Interfacial parameters in correlation with anti-icing performance. Issue 9 (4th July 2021) - Nguyen, Ba Duc; Cao, Binh Xuan; Do, Thuy Chi; Trinh, Ha Bich; Nguyen, Thanh-Binh
ABSTRACT: In this work, we investigated the correlation between interfacial parameters with anti-icing performance in terms of adhesive strength. Samples with different morphologies and surface energies ranging from superhydrophilic to superhydrophobic were evaluated in relationship with contact angle, contact angle hysteresis, water – glass work of adhesion and ice-glass work of adhesion. Superhydrophobic surfaces with well-textured nanopillars were fabricated via dry etching process following by low-energy chemical compound coating. In addition, flat quartz substrates with low wetting states achieved through UVO expose method were also examined. The results demonstrated the relationship between interfacial parameters and anti-icing performance with important considerations on surface coating material and wetting state. This insight should lead to an understanding of icing phenomena and the design of icephobic surfaces.